Calculation of Motor Vehicle Insurance Premiums by using the Moment Method to Estimate the Aggregate Claim Model - Sultan Izbik Riska Alfaridzi; Agung Prabowo; Nunung Nurhayati; Nurfadhlina Abdul Halim (Research Collaboration Community (RCC), 2024)
The aggregate claim model is a model that can be used to determine the amount of premium billed to the insured by the insurance company. This model consists of a combination of two independent random variables, namely the number of claims that occur and the size of the claim for each claim submitted. In this study, many claims are Poisson distributed and the size of the claim is exponentially distributed. The method of moments is used to estimate the parameters of each distribution. Based on the calculation results, the amount of premium billed to the insured for one year if based on the pure premium principle is Rp. 112,500,000.00 and if based on the expected value principle, variance value principle, and standard deviation principle is Rp. 165,900,000.00.